In vitro Biomechanical Analysis of Proximal Phalangeal Osteotomy Fixation - Deschuyffeleer, Sten; Duerinckx, Joris; Caekebeke, Pieter (Journal of Wrist Surgery, 2021)
Background Corrective osteotomies of the proximal phalanx are typically stabilized with plate and screws. Although intramedullary headless screws form an alternative fixation method in the treatment of acute phalangeal fractures, reports about fixation of opening wedge corrective osteotomies with these implants are lacking.Objective The goal of the present study was to biomechanically compare the failure force of both fixation methods for this specific indication.Methods Twenty-four cadaver phalanges were equally distributed between apex volar and apex lateral opening wedge osteotomy groups. In each group, half of the osteotomies were fixed with a 1.3-mm dorsal locking plate, the other half with a 2.4-mm intramedullary headless screw. A three-point bending test was performed.Results The mean maximal failure force after apex lateral osteotomy was 178.4 N for the plate-screw construct and 144.0 N after intramedullary headless screw fixation. After apex volar osteotomy, mean maximal force was 237.6 N in the plate-screw group and 160.9 N in the intramedullary headless screw group. Mean stiffness after apex lateral osteotomy was 63.3 N/mm in the plate-screw group, and 55.9 N/mm in the intramedullary headless screw group. Mean stiffness after apex volar osteotomy was 197.5 N/mm and 60.0 N/mm for the plate-screw and intramedullary headless screw group, respectively.Conclusion For apex volar osteotomies, dorsally applied angular stable plate and screws provide significantly stronger fixation than intramedullary headless screws. For apex lateral osteotomies, fixation force is comparable.Clinical relevance These data are useful when considering fixation of opening wedge osteotomies with intramedullary screws.
Keywords: corrective osteotomy; proximal; phalanx; intramedullary screw; plate